Declining foreign enrolment at higher education institutions in the United States: a research note - Naidoo, Vik (Sage Publications, Inc, 2007)
When the Institute of International Education reported a drop of 2.4% in international student enrollment in the United States in 2003/2004, the first absolute decline in foreign enrollments since 1971/1972 (Open Doors, 2004), many were quick to point fingers at visa policies instituted after the September 11, 2001 attacks. The “Visas Mantis” review—a security clearance required for foreign students studying any of roughly 200 scientific fields—was blamed for tarnishing the view of the United States as a welcoming place for international students. Although the review has certainly been the cause of increased visa delays and rejections, this article takes the view that it is not the only cause for the dip in foreign enrollments in the United States. Through econometric analyses, it is shown that other than the visa quagmires, improved access to domestic education opportunities and tuition fee increases can indeed explain the drop in foreign enrollments.